Detecting Change in Activity Using the Patient-Specific Functional Scale With Breast Cancer Survivors. Issue 2 (April 2018) - Davies, Claire C.; Lengerich, Alexander; Bugajski, Andrew; Brockopp, Dorothy
Abstract : Background: Breast cancer survivors (BCSs) commonly report physical impairments in the upper extremity following treatment. Identifying and measuring active daily living limitations of BCSs can direct interventions. Presently, psychometrically tested outcome measures for BCSs are limited. Objective: To investigate the responsiveness of the Patient-Specific Functional Scale (PSFS) compared with the Disability of the Arm, Shoulder, and Hand (DASH) questionnaire in BCSs and identify common activity limitations BCSs reported using the PSFS. Methods: Forty female BCSs were referred to a community hospital–based outpatient physical therapy clinic following a mastectomy. The PSFS and the DASH questionnaire were assessed at initial evaluation and discharge. Active shoulder range of motion (ROM) and pain were measured to construct a pooled index. A standard response mean was calculated to determine the internal responsiveness of the PSFS. Results: A significant correlation was found between the PSFS change and ROM change of r s = 0.466 ( P = .003) but not between the DASH and ROM change scores: r s = 0.098 ( P = .558). The PSFS has a significantly higher standardized response mean of 1.2701 than the DASH questionnaire (0.5244). Common activity limitations reported by BCSs are reaching, mopping, sweeping, and dressing. Limitations: No standardization regarding the order of the evaluations may have introduced bias. Conclusions: The PSFS detects change in activity over time in BCSs. The PSFS allows individuals to report their specific activity limitations. Awareness of common activity limitations reported by BCSs can influence interventions.